Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 194756 by horsebrand11 last updated on 15/Jul/23

      b

b

Answered by cortano12 last updated on 15/Jul/23

  ((x−a)/( (√x)+(√a))) = ((x−a)/(3((√x)+(√a)))) +2(√a)   ((3(x−a))/(3((√x)+(√a))))−(((x−a))/(3((√x)+(√a)))) = 2(√a)    ((2(x−a))/(3((√x)+(√a)))) = 2(√a)      ⇒2x−2a = 6(√(ax))+6a      ⇒2x−8a = 6(√(ax))     ⇒x−4a = 3(√(ax))     ⇒x^2 −8ax+16a^2 = 9ax     ⇒x^2 −17ax+16a^2 =0    ⇒(x−16a)(x−a)=0, x=a (reject)     ⇒  determinant (((x=16a)))

xax+a=xa3(x+a)+2a3(xa)3(x+a)(xa)3(x+a)=2a2(xa)3(x+a)=2a2x2a=6ax+6a2x8a=6axx4a=3axx28ax+16a2=9axx217ax+16a2=0(x16a)(xa)=0,x=a(reject)x=16a

Commented by Rasheed.Sindhi last updated on 15/Jul/23

x=a doesn′t satisfy in general.It  satisfies only when x=a=0.

x=adoesntsatisfyingeneral.Itsatisfiesonlywhenx=a=0.

Commented by cortano12 last updated on 15/Jul/23

yes sir. right

yessir.right

Commented by Frix last updated on 15/Jul/23

x=a=0 is not allowed because ((...)/( (√x)+(√a))) ⇒  (√x)+(√a)≠0

x=a=0isnotallowedbecause...x+ax+a0

Commented by Rasheed.Sindhi last updated on 15/Jul/23

Sorry for mistake Sir!

SorryformistakeSir!

Answered by Rasheed.Sindhi last updated on 15/Jul/23

 ⋮  x−a

xa

Answered by Frix last updated on 15/Jul/23

x>0∧a>0  (√x)+(√a)=t>0 ⇔ t−(√a)>0 ⇔ x=(t−(√a))^2   Inserting:  t−2(√a)=((t+4(√a))/3)  t=5(√a)  x=(5(√a)−(√a))^2 =16a

x>0a>0x+a=t>0ta>0x=(ta)2Inserting:t2a=t+4a3t=5ax=(5aa)2=16a

Terms of Service

Privacy Policy

Contact: info@tinkutara.com